2000
DOI: 10.1592/phco.20.16.327s.35006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Value of Pharmacists' Health‐Systemwide Services: Clinical Pathways and Treatment Guidelines

Abstract: Practice guidelines and clinical pathways are increasingly being used as tools to enhance the quality of health care services and to manage costs better. This article reviews the role of guidelines and clinical pathways in health care as defined within the broader concept of practice policies. The factors that increase the effectiveness of practice policies are examined. These include the origin of development, dissemination technique, and implementation strategy. Policies that are internally developed and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…These pathways required multiple documents, including order sets, educational materials, and variance reporting documents. 6 The patient chart and clinical pathway were usually located at the patient bedside, allowing limited staff to gain access to relevant documents at the same time. After integration of EMRs, all staff can access patient records and the clinical pathway for their treatment.…”
Section: Paper Pathway Use and Processmentioning
confidence: 99%
See 2 more Smart Citations
“…These pathways required multiple documents, including order sets, educational materials, and variance reporting documents. 6 The patient chart and clinical pathway were usually located at the patient bedside, allowing limited staff to gain access to relevant documents at the same time. After integration of EMRs, all staff can access patient records and the clinical pathway for their treatment.…”
Section: Paper Pathway Use and Processmentioning
confidence: 99%
“…Clinical guidelines are based upon primary evidence, extensive analysis, and discussion amongst field experts to establish expectations for best practices. 6 Clinical pathways are operational tools for executing best practices based upon local practice and clinical guidelines that are shaped by interdisciplinary teams. These pathways create a consistent workflow for care delivery.…”
Section: History and Evolution Of Clinical Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ICU, the value of the pharmacist is especially important. Pharmacists obtain medication histories; develop and manage policies and protocols for optimal patient care, drug expenditures, and cost avoidance (i.e., analgesia, anticoagulation, delirium, pharmacokinetic, sedation, and transfusion guidelines); optimize antimicrobial stewardship; respond to resuscitation events; verify accuracy of computerized order entry; educate other ICU personal; assist in discussing treatment modalities with patients and/or families; prospectively evaluate drug therapy; and monitor and identify ADRs [398][399][400][401][402][403][404][405][406][407][408][409][410]. The impact of the clinical pharmacist in the ICU has significantly decreased ADRs, antimicrobial resistance, medication costs, transfusions, hemorrhage, ventilator days, and length of stay.…”
Section: Strategies To Decrease Icu Adrsmentioning
confidence: 99%
“…Pharmacists are pharmacotherapy experts, and possess pivotal skills which qualify them for playing active roles in the process of designing and application of clinical pathways (CPs) [ 1 , 2 ]. Literature has consistently reported that CPs can be differentiated from guidelines [ 3 , 4 ] in that CPs are time-bound patient care plans which aim to improve the quality of patient-care and optimize utilization of institutional resources [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%